2018
DOI: 10.1002/cam4.1680
|View full text |Cite
|
Sign up to set email alerts
|

Survival effect of different lymph node staging methods on ovarian cancer: An analysis of 10 878 patients

Abstract: BackgroundTo compare the survival impact of several lymph node staging methods and therapeutic role of lymphadenectomy in patients with epithelial ovarian cancer who had undergone lymphadenectomy.MethodsData were retrospectively collected from the Surveillance, Epidemiology, and End Results program between 1988 and 2013.ResultsAn increasing number of resected lymph nodes (RLNs) was associated with a significant improvement in survival of FIGO stage II and III disease. However, for FIGO stage IV patients, bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Lymph node ratio (LNR), defined as the ratio of the number of metastatic lymph nodes (MLNs) to the number of resected lymph nodes (RLNs)11, has been proved as an independent prognostic predictor in several malignancies including nonsmall cell lung cancer12, breast cancer13, cervical cancer14, endometrial cancer15, and EOC 8, 16-19. However, the previous studies investigated the survival predictive value of LNR in all histologic subtypes of EOC and did not validate their results in another independent population 8, 16-19…”
Section: Introductionmentioning
confidence: 99%
“…Lymph node ratio (LNR), defined as the ratio of the number of metastatic lymph nodes (MLNs) to the number of resected lymph nodes (RLNs)11, has been proved as an independent prognostic predictor in several malignancies including nonsmall cell lung cancer12, breast cancer13, cervical cancer14, endometrial cancer15, and EOC 8, 16-19. However, the previous studies investigated the survival predictive value of LNR in all histologic subtypes of EOC and did not validate their results in another independent population 8, 16-19…”
Section: Introductionmentioning
confidence: 99%
“…Other research, directed by Wang et al . [ 20 ], has also shown that an increasing number of resected lymph nodes correlated with a significant improvement in OS for FIGO stage II and III cases of the disease. However, for FIGO stage IV patients, an improved OS was not significantly associated with a more extensive lymphadenectomy.…”
Section: Discussionmentioning
confidence: 98%
“…[ 18 ] showed that a value greater than 3 PLN is an independent predictive factor in a poor prognosis for patients with clear cell OC aside from the number of lymph nodes removed (comparing groups with < 10 removed and > 10 removed) [ 18 ]. However, the number of PLN is dependent on many factors, such as the surgeon’s and pathologist’s experience, anatomical variation, or the extent of the tumor [ 19 ], and this PLN figure does not provide or infer any information about the number of negative lymph nodes [ 20 ]. It is why the LNR value has been found in several studies to be a more accurate predictor [ 15 , 17 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A value of 0.5 is added to both numerator and denomination to avoid singularity ( 15 , 16 ). The LODDS also showed superiority in predicting outcomes in bladder ( 17 ), colorectal ( 18 ), lung ( 19 ), ovarian ( 20 ), and esophageal ( 21 ) cancers. In this study, we performed a large population-based database investigation of the prognostic values of RLNs, PLNs, NLNs, LNR, and LODDS in SBNETs, which may inform treatment options and prognosis discussions and guide eligibility for clinical trials.…”
Section: Introductionmentioning
confidence: 99%